Whey and Cow Milk: Dairy Products Useful for Crop Protection - Gonson, Fanny; Taylor, Alex; Marchand, Patrice Andre (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted during spring and summer 2022 at Mare Savin garden centre (Trappes, France) to confirm plant protection properties of some dairy products. Indeed, for crop protection, the search for new non-chemical fungicides useful, durable, affordable and efficient as active substances (a.s.). These suitable products, especially from natural origin called BioControl Agents (BCA) are acceptable to civil society (i.e., low-concern profile, and absence of residues of concern) are of paramount importance as the number of chemical solutions has drastically decreased in recent years. When natural substances from the plant origin are plethoric in literature and some are approved as Plant Protection Product (PPP), natural substances from the animal origin repertoire are sparsely represented in PPP a.s., but lately a few substances have obtained a European Union (EU) active substance approval (i.e. sheep fat, blood meal, fish oil, chitosan hydrochloride from crab shell). Dairy products may also exhibit crop protection properties like whey and cow milk are two of these new BCAs. The corresponding applications under EU PPP regulation (EC) n° 1107/2009 were granted as basic substance according Article 23, respectively in 2016 for whey and 2020 for cow milk for protection of vegetable against mildew and agricultural tools disinfection. These basic substances are approved for an unlimited period of time with no Market Authorisation, for all Europe without zone or Member State consideration, and with no Maximum Residue Limits (MRL). Later, an extension of use for vineyards protection against diseases was granted for whey in 2021.